An exploratory study of prevalence of mental retardation in mysore city - Bharath Raj J (Journal of All India Institute of Speech and Hearing, 1971)
It is recognised long since that mental retardation is one of serious afflictionsof mankind, in terms of its magnitude and dire consequences to the sufferer,his family and the society in which he lives. As elsewhere, this clinical conditionremained outside the centre of interest, both for the professionals and the publicin our country also. An awareness has now come among the related professionalpeople to make a serious study of it, in all its ramifications. There has been oflate, an increasing participation of various professional groups as Psychologists,Psychiatrists, Educationists, Paediatricians and Social Workers. The growingimportance of this field is evidenced by the coming into being of an All IndiaAssociation of Mental Retardation (A.I.A.M.R.) and the All India level conferencesit successfully organised at Chandigarh in 1965, 1967 and at New Delhi in 1966,and the Indian Journal of Mental Retardation whose first volume appeared in1968.